Grazing, abandonment and frequent mowing inﬂuence the persistence of the steppe marmot, Marmota bobak - Savchenko, Galina; Ronkin, Vladimir (Hacquetia, 2018)
The goals of the study were to illustrate how parameters of steppe marmot settlements change after abandonment of livestock grazing, to evaluate diﬀerences in vegetation characteristics between grazed and abandoned habitats, to find the links between these characteristics and the persistence of marmot settlements and to establish whether it is possible to maintain the food base of marmots by applying frequently repeated mowing. Data were collected in 1991–2016 in the steppe marmot (Marmota bobak) settlement in the Regional Landscape Park “The Velykyi Burluk-Steppe” (Kharkiv Region, Northeastern Ukraine). We found that grazing prolongs the period of active plant growth and supports a regrowth during periods of intensive feeding of all age groups of marmots. In abandoned habitats the vegetation period ended before the end of active feeding of reproductive females and juveniles. Tis resulted in lower reproductive success, which determines a decrease in the population and may in the future result in a larger decline of settlements. Frequently repeated mowing by a lawnmower at a cutting height of 6–9 cm prolongs the vegetation period and maintains a water content in the plants similar to that of grazed habitats throughout the active season of steppe marmots.